2017
DOI: 10.1109/access.2017.2685434
|View full text |Cite
|
Sign up to set email alerts
|

A Survey on Mobile Edge Networks: Convergence of Computing, Caching and Communications

Abstract: As the explosive growth of smart devices and the advent of many new applications, traffic volume has been growing exponentially. The traditional centralized network architecture cannot accommodate such user demands due to heavy burden on the backhaul links and long latency. Therefore, new architectures which bring network functions and contents to the network edge are proposed, i.e., mobile edge computing and caching. Mobile edge networks provide cloud computing and caching capabilities at the edge of cellular… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
476
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 832 publications
(480 citation statements)
references
References 147 publications
(237 reference statements)
1
476
0
3
Order By: Relevance
“…To enlarge the utmost benefits to facilitate network‐wide content replication, ICN is proposed to equip router with caches. Interestingly, in the work of Roberts and Sbihi, there also exists ICN, which ambitions to change the mode of retrieving the contents on the internet by uniquely naming the content and smart distribute these across the network, instead than conventionally having one source for the content access . It was also shown that most of the caching acquisitions in ICN can be acquired by caching at the edges of the network using existing CDNs, contrary to the popular belief that caching close to users is highly inefficient.…”
Section: Network Cachingmentioning
confidence: 99%
“…To enlarge the utmost benefits to facilitate network‐wide content replication, ICN is proposed to equip router with caches. Interestingly, in the work of Roberts and Sbihi, there also exists ICN, which ambitions to change the mode of retrieving the contents on the internet by uniquely naming the content and smart distribute these across the network, instead than conventionally having one source for the content access . It was also shown that most of the caching acquisitions in ICN can be acquired by caching at the edges of the network using existing CDNs, contrary to the popular belief that caching close to users is highly inefficient.…”
Section: Network Cachingmentioning
confidence: 99%
“…Clouds may be limited to a single organization (enterprise cloud), be available to many organizations (public cloud) or a combination of both (hybrid cloud). The cloud computing architecture has two layers: the end devices (the bottom layer) and the cloud servers (the top layer) (see Figure ) …”
Section: Related Workmentioning
confidence: 99%
“…The disadvantage of edge computing is the limited processing power and storage capacity of the edge servers. The edge computing architecture has three layers: the end devices (the bottom layer), the edge servers (the intermediate layer), and the cloud servers (the top layer) (see Figure ) …”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, as D2D communications gain research attentions, caching on terminal devices also starts to show its significance [62]. For that reason, researchers are making efforts to answer questions around caching such as where to cache (placement) [63,64], what to cache (content type, popularity, and mobility awareness) [65], and how to cache (replacement policies) [66,67]. In this work, we adopt the idea of caching for vector tile sharing, and we thus introduce the definition of vector tile layers and naming scheme for data caching and exchanging.…”
Section: Caching For Data Disseminationmentioning
confidence: 99%